2022
DOI: 10.3758/s13428-021-01768-2
|View full text |Cite
|
Sign up to set email alerts
|

Web-based language production experiments: Semantic interference assessment is robust for spoken and typed response modalities

Abstract: For experimental research on language production, temporal precision and high quality of the recorded audio files are imperative. These requirements are a considerable challenge if language production is to be investigated online. However, online research has huge potential in terms of efficiency, ecological validity and diversity of study populations in psycholinguistic and related research, also beyond the current situation. Here, we supply confirmatory evidence that language production can be investigated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Data quality was good, where 99% of the audios were transcribable (99% of produced words being transcribed), and only about 12% of participants were replaced due to incomplete or missing recordings. In addition, web-based language production paradigms (e.g., picture-naming tasks) have reproduced lab-based findings across studies (Fairs & Strijkers, 2021;Vogt et al, 2021;Stark et al, 2022). Therefore, the quality of auditory data collected online does not seem to be compromised by technical issues and human factors.…”
Section: Introductionmentioning
confidence: 83%
“…Data quality was good, where 99% of the audios were transcribable (99% of produced words being transcribed), and only about 12% of participants were replaced due to incomplete or missing recordings. In addition, web-based language production paradigms (e.g., picture-naming tasks) have reproduced lab-based findings across studies (Fairs & Strijkers, 2021;Vogt et al, 2021;Stark et al, 2022). Therefore, the quality of auditory data collected online does not seem to be compromised by technical issues and human factors.…”
Section: Introductionmentioning
confidence: 83%
“…Several studies have demonstrated the feasibility and accuracy of web-based language production studies. Although overall latencies are longer in web-based than in lab-based experiments (Fairs & Strijkers, 2021), frequently-observed psycholinguistic effects that rely on precise and accurate measurement of naming latencies are replicated (Stark et al, 2022;Vogt et al, 2021).…”
Section: Research Questionsmentioning
confidence: 99%
“…Raletedness aids, and interferes with, lexical (and conceptual) selection in different ways. Semantic interference, which also is being used as a research paradigm (i.e., Bürki, Elbuy, Madec, & Vasishth, 2020;Stark, van Scherpenberg, Obrig, & Rahman, 2021), is the effect of different related or unrelated distractor words (or images) that can lead to further exploration of the semantic space or to cognitive fixedness.…”
Section: Perspective From a Cognitive Basismentioning
confidence: 99%